1998
DOI: 10.1079/bjn19980005
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in mood after changing to a low-fat diet

Abstract: The effects on mood of reducing dietary fat while keeping the energy constant were examined in ten male and ten female healthy volunteers aged between 20 and 37 years. Each volunteer consumed a diet containing 41 % energy as fat for 1 month. For the second month half of the subjects changed to a low-fat diet (25 % energy from fat) and the remainder continued to eat the diet containing 41 % energy from fat. Changes in mood and blood lipid concentrations were assessed before, during and at the end of the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 29 publications
1
35
0
1
Order By: Relevance
“…Thus, withdrawing palatable food activated the stress-related CRF peptide system in the central nucleus of the amygdala, analogous to findings in models of drug and ethanol withdrawal (7,8). Because renewed access to palatable food decreased extrahypothalamic CRF system activation in the central nucleus of the amygdala, wherein CRF activation is linked to anxiety (16), the present results also suggest that palatable food might acquire negative reinforcing properties by relieving negative affective consequences of abstinence (17).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, withdrawing palatable food activated the stress-related CRF peptide system in the central nucleus of the amygdala, analogous to findings in models of drug and ethanol withdrawal (7,8). Because renewed access to palatable food decreased extrahypothalamic CRF system activation in the central nucleus of the amygdala, wherein CRF activation is linked to anxiety (16), the present results also suggest that palatable food might acquire negative reinforcing properties by relieving negative affective consequences of abstinence (17).…”
Section: Resultssupporting
confidence: 61%
“…Thus, addiction-like changes in CRF 1 systems may help drive (i) intake of energy-dense palatable foods, (ii) underconsumption of healthier alternatives, and (iii) the associated negative emotional state that occurs when access to palatable food is prevented (4,5,(10)(11)(12)17). Translated to the human condition, CRF system activation may promote relapse eating in obesity and related eating disorders as well as other negative motivational sequelae of cyclic abstinence from palatable food.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of adverse mood effects of cholesterol reduction generally derive from relatively small studies. 15,35,36 With respect to aggression and violent behavior, a variety of observational studies have found, compared with that of controls, lower mean TC concentrations in violent criminals, violent psychiatric patients, individuals with antisocial personality disorder, and the victims of death from suicides, accidents, and violence. [1][2][3][4][5][37][38][39] As noted earlier, in placebo-controlled clinical trails, deaths from suicides, accidents, and violence may be increased by diet modifications and older cholesterol-lowering medications, but such does not appear to occur with statin drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A low-fat diet was shown to increase anger-hostility and tension-anxiety parameters compared to isocaloric control diet (Wells, Read, Laugharne, & Ahluwalia, 1998). On the other hand, a low-carbohydrate (hi-fat) diet, also isocaloric, had a similar effect, in addition to a decrease in physical performance (Butki, Baumstark, & Driver, 2003;Filaire, Maso, Degoutte, Jouanel, & Lac, 2001).…”
Section: Introductionmentioning
confidence: 79%
“…We saw above that several specific diets low-fat (Wells et al, 1998) as well as high-fat (Butki et al, 2003;Filaire et al, 2001) correlated with changes in mood and cognitive and physical performance. Other diet changes influenced other traits (Markus et al, 2000).…”
Section: Discussionmentioning
confidence: 99%